Electro-mechanical single acting pulley rubber V-belt continuously variable transmission (EMSAP RVB-CVT) for scooter - Nur, Cholis (2013)
The rubber v-belt continuously variable transmission (RVB-CVT) in motorcycle is very important because it affects good drive ability in terms of response and smoothness for the rider or passenger. RVB-CVT mechanically consists of primary clutch, secondary clutch and V-belt. The new mechanism of mechanical RVB-CVT components with electric motor is introduced. The objectives of this thesis are to design and to simulate a new actuate the electro-mechanical single acting pulley rubber V-belt continuously variable transmission. The electro-mechanical single acting pulley rubber V-belt continuously variable transmission (EMSAP RVB-CVT) system consists of two sets of pulleys, primary pulley and cam mechanism placed on input fixed shaft and secondary pulley placed on the secondary fixed shaft. The primary pulley design changes to reduce the centrifugal force generated by the mass of the weights and clutch spring, replaced the cam mechanism which is controlled by a DC motor through a gear's mechanism. Each set of the pulley has two moveable sheaves that can be shifted axially along the shaft. A spring is inserted in the back of the secondary pulley sheave to provide continuous clamping force to the belt and to reduce excessive slip during transmission ratio change. Solidwork software used to drawing detail of EMSAP RVB-CVT. Simulation using Matlab and Simulink software to determine the CVT ratio obtained in addition to get the response of the design that has been created. The results show that a new design of EMSAP RVB-CVT is successfully design and simulate. The computer simulation result is present the Proportional, Integral and Derivative (PID) controller model works satisfactory for desired ratio transmission.